NEW DATA ON FAST VARIABILITY OF THE Hα PROFILE IN THE SPECTRA OF YOUNG Ae-Be HERBIG STARS FROM "P CYG" SUBGROUP - Pogodin, M. A. (Одеські астрономічні публікації, 2017)
The variability of the Hα profile of 2 A0e Herbig stars HD 163296 (ESO, CAT+CES, July, 1991, 1992, 35 Spectra) and AB Aur (CrAO, ZTSh + Coude-spectrograph, January 1993, 45 spectra). Significant variability of the P Cyg-type profile of both objects was detected with time scales from hours to months. Two main types of hour-scale variability are found: a) monotonous changes of arbitrary intensity of different parts of the line (both stars), b) episodic appearance of local spectral details at variable wavelength which may be owed to inhomogeneities of the circum-stellar medium (HD 163296 only). Periodicity of the profile of the absorption component in AB Aur with P = 70h an 35h is suspected. A simple geometric model of the circumstellar shell is proposed for similar objects with variable equator-concentrated stellar wind and a relatively quiet outer shell.